PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO DENGAN TIPE MAKE A MATCH DALAM PEMBELAJARAN BIOLOGI (STUDI TENTANG AKTIVITAS, RESPON, DAN HASIL BELAJAR SISWA) - Ryan Humardani Syam Pratomo (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2017)
This research is aimed at: (i) identifying the difference of students’ activity at grade IX of SMPN 1 Sungguminasa who were taught using cooperative learning type the power of two and type make a match (ii) finding the difference of students’ response at grade IX of SMPN 1 Sungguminasa who were taught by using cooperative learning of type the power of two and type make a match (iii) discovering the difference of students’ learning outcome at grade IX of SMPN 1 Sungguminasa who were taught by using cooperative learning of type the power of two and type make a match. Type of this research is quasi experiment that was conducted at SMPN 1 Sungguminasa. There were two group of experiment involved on this research; those are group experiment I who were taught by using cooperative learning type of the power of two and group experiment II who were taught by using cooperative learning type make a match. Instrument of the research include observation sheet of activities to know the students’ activities, questionnaire to discover students’ response on the learning activities, learning outcomes test to obtain data the learning outcomes of the subject Human Survival. The data were than analyzed descriptively and inferentially (t-test with α = 0.05) by the assist of SPSS 15.0 for windows. The result indicates that: (i) there is no significant difference between activities of students who were taught by using cooperative learning type the power of two and type make a match, (ii) there is no significant difference between responses of students who were taught by using cooperative learning type the power of two and type make a match, and (iii) there is no significant difference between learning outcomes of students who were taught by using cooperative learning type the power of two and type make a match.